The Effectiveness Of Green Bonds In Promoting Sustainable Finance: A Meta-Analysis - Andi Harmoko Arifin; Nurul Hudaeni; Abdul Rasyid; Suhardi Suhardi; Degdo Suprayitno; Finny Redjeki; Titik Purwati; andi Sri Rezky Wulandari (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
The growing emphasis on environmental sustainability has driven the growth of green bonds as an important instrument in sustainable financing. This study conducted a comprehensive meta-analysis to evaluate the effectiveness of green bonds in supporting sustainable financing in various sectors and regions. By analyzing 20 peer-reviewed articles and empirical studies published between 2020 and 2024, the study synthesized quantitative findings to examine the influence between green bonds and key indicators of sustainable finance, including environmental impact, investor confidence, and financial performance. Data analysis with the help of JASP. The results show that green bonds significantly contribute to reducing carbon emissions and encouraging renewable energy projects, as well as attracting investors who care about the environment with a value (g = 0.937; p < 0.05). However, the analysis also reveals regional disparities in adoption and effectiveness, which are influenced by regulatory frameworks, market maturity, and institutional support. In addition, the study highlights challenges such as greenwashing and inconsistent reporting standards, which can reduce the credibility of green bonds.